Impact of Urban Surfaces on Microclimatic Conditions and Thermal Comfort in Burdur, Türkiye - Zhang, Maomao; Yigit, Ilker; Adiguzel, Fatih; Hu, Chunguang; Chen, Enqing; Siyavus, Ahmet Emrah; Kaya, Asir Yuksel (Mdpi, 2024)
Rapid urbanization worldwide offers numerous benefits but also introduces challenges, particularly concerning urban climate comfort, which affects the physical and social well-being in cities. This study examined the microclimatic characteristics of the Bur & ccedil; neighborhood in the historical core of Burdur city, using ENVI-Met models with temperature, relative humidity, wind and PET data collected over a 33,665 m2 area at 06:00, 09:00, 12:00, 15:00, 18:00 and 21:00 on 15 August 2023. The analysis revealed that thermal comfort decreases significantly from 09:00 onwards, especially on hard surfaces like asphalt, concrete and parquet, which lack vegetation and intensify heat retention. By contrast, green areas were found to enhance bioclimatic comfort by reducing perceived temperatures by up to 20% in shaded and vegetated zones. Based on these findings, it is recommended that urban areas reduce heat-absorbing materials, such as asphalt and concrete and prioritize green spaces in landscape planning to improve thermal comfort and create more sustainable urban environments.
Keywords: urban; climate; microclimate; environment; land use